Masculinities in the Gospel of Matthew: Joseph, John, Peter, and Judas - Mohn, Kendra A. (Lexington Books/Fortress Academic, 2024)
Kendra A. Mohn traces how the constructions of nonelite men in the Gospel of Matthew negotiate expectations of elite Roman masculinity. Highlighting wealth, divine service, and dominating control, Mohn shows how the depictions of Joseph, John, Peter, and Judas shape expectations of men in terms of discipleship, power, and leadership.